Impacts of anterior-posterior jaw disproportions on speech of dentofacial disharmony patients. (29th October 2022) - Oliver, Steven; Keyser, Mary Morgan Bitler; Jhingree, Samantha; Bocklage, Clare; Lathrop, Hillary; Giduz, Natalie; Moss, Kevin; Blakey, George; White, Raymond; Turvey, Timothy; Mielke, Jeff; Zajac, David; et al.
Summary: Background/Objectives: Articulation problems impact communication, development, and quality of life, and are diagnosed in 73–87% of patients with Class II Dentofacial Disharmony (DFD). We evaluated whether differences exist in stop (/t/ or/k/), fricative (/s/ or/ʃ/), and affricate (/tʃ/) consonant sounds of Class II DFD subjects, and whether extent of malocclusion correlates with severity of speech distortion. We hypothesized that Class II patients display milder distortions than Class III and anterior open bite (AOB), as Class II patients can posture into a Class I occlusion. Materials/Methods: Audio and orthodontic records were collected from DFD patients ( N = 53-Class II, 102-Class III, 72-Controls) who were pursuing orthodontics and orthognathic surgery. A speech pathologist perceptually scored speech. Acoustic differences in recordings were measured using Spectral Moment Analysis. Results: When Class II subjects were compared to controls, significant differences were found for the centroid frequency (M1) of the /s/ sound and the spectral spread (M2) of /t/, /tʃ/, and /s/ sounds, with pairwise significance for controls relative to Class II AOB and all Class II subjects. Class II AOB subjects had higher M1 and M2 values than patients with Class II closed bites and Class I controls for most sounds. When comparing across anterior-posterior (AP) groups, differences exist between controls, Class II and III DFD subjects for M1 of /t/, /tʃ/, and/ʃ/ and M2 for /t/, /tʃ/, /s/, and /ʃ/ sounds. Using linear regression, correlations between Class II and III severity and spectral measures were found for /t/ and /tʃ/ sounds. Conclusions/Implications: Class II and III patients have a higher prevalence of qualitative distortions and spectral changes in consonants compared to controls, but Class II spectral shifts are smaller and affect fewer sounds than in Class III and AOB cohorts. Linear correlations between AP discrepancy and spectral change suggest causation and that treatment may improve articulation problems.